Effect of Na2 WO4 Concentration on the Properties of Micro-arc Oxidation Coating of ZM6 Magnesium Alloy - GUO Jia-qi; GUO Er-jun; FENG Yi-cheng; WANG Li-ping; JIANG Wen-yong (Journal of Harbin University of Science and Technology)
The test uses ZM6 magnesium alloy as the experimental material，the micro-arc oxidation power supply uses a constant pressure mode，and the performance of the micro-arc oxidation film layer is performed by a scanning electron microscope ( SEM) ，X-ray diffractometer ( XＲD) ，Vickers hardness tester and electrochemical workstation. The effect of different concentration of Na2WO4 additive in silicic acid system on the surface morphology，phase composition and corrosion resistance of micro arc oxidation layer of ZM6 magnesium alloy was studied. The experimental results show that the addition of Na2WO4 can effectively improve the surface morphology and properties of the films. With the increase of Na2WO4 concentration，the corrosion resistance first increased and then decreased. When the Na2WO4 concentration is 1 g /L，the film quality and corrosion resistance are the best; the film phase is mainly composed of MgO，Mg2 SiO4 and a small amount of WO3 ; the self-corrosion potential is － 1. 482 247 V，and the corrosion current is 0. 146 μA.